LEGAL PROTECTION AGAINST DOMESTIC VIOLENCE IN CHILD MARRIAGE - Dewi Judiasih, Sonny; Kusmayanti, Hazar (Fakultas Hukum Universitas Padjadjaran, 2024)
The aim of law enforcement is none other than to ensure that legal subjects obtain every right. One law enforcement that must be considered is in the field of family law in marriage law. Marriage of children under the age of 18 is vulnerable to domestic violence. This research will enforce legal protection against domestic violence in child marriages, whether legalized by the state or child marriages carried out through sirri marriages.. The method used is juridical qualitative with a descriptive approach and the data is processed in a qualitative juridical manner. The results of the study show that there are differences in the legal protection of victims of domestic violence in sirri child marriages. Legal child marriage and obtaining marriage dispensation can be protected by Law No. 23 of 2004 concerning the Elimination of Domestic Violence and other relevant laws and regulations. Meanwhile, the protection of domestic violence in a sirri / unregistered child marriage can only be subject to the Criminal Code and Law No. 35 of 2014 concerning Child protection.